The Impact of Asset Recovery Regulations on Corruption Cases in Indonesian: A Leap Forward? - Fithriatus Shalihah; Bakhshillo Kamolovich Khojaev; Fitrat Umirov; Mohammad Ishaque Husain; Deslaely Putranti (Contrarius, 2026)
The central problem lies in the structural limitations of the asset recovery regime under the Anti-Corruption Law, which requires a criminal conviction for confiscation. This restriction has hindered full recovery of state losses, particularly in cases involving hidden or transferred assets and transnational challenges. The research aims to assess the paradigmatic nature of Indonesia’s asset forfeiture reform by analysing its conceptual transformation, constitutional legitimacy, and systemic coherence. This research employs a normative juridical method, relying on statutory, conceptual, and comparative approaches. The research reveals that, first, the shift from conviction-based forfeiture to non-conviction-based (NCB) forfeiture reflects an emerging transformation from offender-oriented justice toward asset-oriented justice. However, in Indonesia, this transformation remains transitional and has not yet restructured the philosophical and institutional foundations of asset recovery. Second, the comparative analysis demonstrates that the United Kingdom has successfully institutionalised civil recovery mechanisms within a strong framework of judicial oversight and proportionality, supported by human rights safeguards, thereby illustrating that effectiveness and constitutional protection are not mutually exclusive. Finally, Indonesia’s reform, while normatively progressive, still depends on harmonisation with constitutional guarantees and requires clearer standards of proof, differentiated procedural safeguards, and stronger institutional coordination to ensure systemic coherence and prevent abuse of power. The research recommends adopting a hybrid-restorative constitutional model of asset forfeiture. Such a model should provide limited autonomy for non-conviction-based confiscation, integrate early asset tracking and freezing mechanisms, apply differentiated standards of proof, and embed strict constitutional safeguards through effective judicial review and proportionality principles.